Design and operation of a 50 kWth Chemical Looping Combustion (CLC) unit for solid fuels. (1st November 2015) - Abad, Alberto; Pérez-Vega, Raúl; de Diego, Luis F.; García-Labiano, Francisco; Gayán, Pilar; Adánez, Juan
Graphical abstract: Design layout of the 50 kWth CLC unit. Highlights: The design of a 50 kWth CLC unit for coal combustion is presented. The CLC unit is considered to be operated both in i G-CLC and CLOU modes. A dual loop seal allowed high solids flow and high solids inventory in fuel reactor. CO2 capture rates and total oxygen demand values are presented for first tests. Low oxygen demand values were obtained and CO2 capture must be optimized. Abstract: A Chemical Looping Combustion (CLC) unit for solid fuels has been designed, erected and operated. The design was based on a thermal power of 20 kWth for in - situ Gasification Chemical Looping Combustion ( i G-CLC) or 50 kWth for Chemical Looping with Oxygen Uncoupling (CLOU). Fuel and air reactors are two interconnected circulating fluidized beds reactors, with the coal being fed at the bottom of the fuel reactor to maximize the contact between the volatile matter and the oxygen carrier particles. A carbon stripper has been included between fuel and air reactors to increase the CO2 capture rates. In this unit, the char particles are separated from the oxygen carrier particles and recirculated to the fuel reactor. The solids flow exiting from the fuel reactor is split into two different streams by using a double loop seal down the fuel reactor cyclone. One goes to the carbon stripper and the other is recirculated to the fuel reactor. In this way it is possible to have an independent control of solids inventory in the fuel reactor and the global solids circulation flow rate between fuel and air reactors. First operational results at steady state have been obtained with stable operation in i G-CLC mode during combustion of a bituminous coal with ilmenite being the oxygen carrier. A CO2 capture value of 88% at 991 °C and a total oxygen demand value of 8.5% were obtained with a solids inventory in the fuel reactor of 470 kg/MWth .